The Establishment of a Community Reading Library in Ngroto Village, Pujon Subdistrict, Malang Regency, as Part of the Implementation of the IDM (Village Development Index) and the Strengthening of the Culture of Literacy - Muhaimin Zulhair Achsin (Universitas Pancasakti Tegal, 2025)
One of the benchmarks for measuring village development in Indonesia is the IDM (Village Development Index). Regulation of the Minister of Villages, Disadvantaged Regions, and Transmigration of the Republic of Indonesia No. 2 of 2016 governs the IDM and its measurement components. In the education dimension, three aspects are measured: access to primary and secondary education, access to non-formal education, and access to knowledge. Regarding access to knowledge, the indicator is the presence of a community reading library or village library. It is through this indicator that the author and team aim to establish a community reading library or village library in Ngroto Village, Pujon Subdistrict, Malang Regency. Although Ngroto Village ranked first in the IDM nationwide in 2018, there is still no community reading library in the village. This is the basis for our community service project. Additionally, the establishment of a reading library and other literacy programs is expected to strengthen intergenerational literacy culture in the village. This community service project took place from May to July 2022.